Impacto de la cotización del dólar en la balanza comercial de bienes: revisión sector industrial 2010-2015 - Echeverry Martínez, Nicolay (Ciencias Administrativas, Económicas y Contables, 2017)
This study describes in general the impact that suffers the commercial balance of goods in Colombia by changes in the exchange rate with its main trading partners, and which encompasses a series of economic events that together can cause imbalances in the economy of the country. The period of evaluation was between 2010 and 2015, which details the situation which arose in the imports and exports of the country in contrast to the average daily contribution of the exchange rate, including balance sheets issued by the Bank of the Republic as a governmental entity to give reports relating to commercial transactions carried out in the balance of payments during the periods in question. In the same way arises the monetary and foreign exchange control and inflation policies that are an essential part in the understanding of statistics displayed in the annual balance sheets showing the State of adequacy of the economy of the country compared to other countries. The statistical data presented through graphs will give us to understand more easily the variations that present the economy relate variables that influence the focus of research.